Circularity in the construction and demolition industry: Comparing weighting methods for multi-criteria decision analysis - Dytianquin, Norman; Kalogeras, Nikos; van Oorschot, John; Abujidi, Nurhan (Frontiers in Sustainability, 2023)
In studying circularity in the construction and demolition industry (CDI) in the EU, five projects in selected EU countries were compared to assess how the application of circularity achieved balance in environment, social and economic dimensions of sustainability. The selected projects involved different stages of the circularity ladder, used diverse design principles and focused on different stages of the construction life cycle, making them interesting comparators for applying circularity in CDI. Selected indicators for the three dimensions included those found in environmental impact and life cycle assessments for environmental criteria; social impact assessments for social criteria and economic feasibility, project appraisal and evaluation reports for economic criteria. In weighting criteria, several methods exist comprising subjective, objective and integrated techniques. The robustness of objective versus subjective weights is rather debatable. In this paper, selected subjective and objective weighting techniques were explored to investigate if substantial differences would occur in the ranking of circular projects in CDI. As weighting of criteria could influence project outcomes, objectivity in weighting is advised. Computational comparisons indicated that subjective methods do not significantly differ from objective ones that use mathematical and statistical formulations. As such, subjective weighting methods still conveniently capture credible results.